Philippine overseas employment guidebook - Martinez, Ma. Luisa P. (Quezon City AIDEC International Marketing and Management Systems, 1989)
This book is geared towards being a standard reference material for the industry's regulations and procedures, statistical analysis, workers' profile and addresses of key personnel of both private and government entities. It also contains the views of the private sector and the government on the industry at large.
Compiled testimony for all industry practitioners.
Keywords: Employment in foreign countries -- Handbooks, manuals, etc